2019
DOI: 10.3390/app9061213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Tip Clearance on the Aeroelastic Characteristics of a Last Stage Steam Turbine

Abstract: In this paper, the tip clearance effects on the aeroelastic stability of a last-stage steam turbine model are investigated. Most of the unsteady aerodynamic work contributing to flutter of the long blades of the last-stage of a steam turbine is done near the tip of the blade. The flow in this region is transonic and sensitive to geometric parameters such as the tip clearance height. The KTH Steam Turbine Flutter Test Case was chosen as the test case, which is an open geometry with similar parameters to modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…When the blades vibrate at different NDs or inter-blade phase angles (IBPA), this effect will be changed, further leading to variations in blade flutter stability [11,12]. In addition, some researches [5,9,13] also found that the effects of tip clearance variations on the flutter stability are distinct at different NDs or IBPAs.…”
Section: Introductionmentioning
confidence: 99%
“…When the blades vibrate at different NDs or inter-blade phase angles (IBPA), this effect will be changed, further leading to variations in blade flutter stability [11,12]. In addition, some researches [5,9,13] also found that the effects of tip clearance variations on the flutter stability are distinct at different NDs or IBPAs.…”
Section: Introductionmentioning
confidence: 99%